2018
DOI: 10.1002/ece3.3980
|View full text |Cite
|
Sign up to set email alerts
|

Age and area predict patterns of species richness in pumice rafts contingent on oceanic climatic zone encountered

Abstract: The theory of island biogeography predicts that area and age explain species richness patterns (or alpha diversity) in insular habitats. Using a unique natural phenomenon, pumice rafting, we measured the influence of area, age, and oceanic climate on patterns of species richness. Pumice rafts are formed simultaneously when submarine volcanoes erupt, the pumice clasts breakup irregularly, forming irregularly shaped pumice stones which while floating through the ocean are colonized by marine biota. We analyze tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 80 publications
(169 reference statements)
3
7
0
Order By: Relevance
“…Debris surface area was also positively correlated with abundance of Lepas, a relationship observed for biofoulers in other studies (Dellinger et al 1997;Velasquez et al 2018). Similarly, Goldstein et al (2014) found a positive correlation between object size and biofouler diversity.…”
Section: Shore-cast Debris Surface Areasupporting
confidence: 57%
See 1 more Smart Citation
“…Debris surface area was also positively correlated with abundance of Lepas, a relationship observed for biofoulers in other studies (Dellinger et al 1997;Velasquez et al 2018). Similarly, Goldstein et al (2014) found a positive correlation between object size and biofouler diversity.…”
Section: Shore-cast Debris Surface Areasupporting
confidence: 57%
“…Surface area of shore-cast debris was strongly positively correlated with maximum length of L. anserifera. This is potentially related to the greater stability of larger, heavier objects (Velasquez et al 2018), with floating behaviour of drifting objects strongly influencing biofouling communities (Bravo et al 2011). Studies using mooring biofouling communities as proxies for those on free-drifting debris may therefore be more accurate when applied to larger, more stable debris.…”
Section: Shore-cast Debris Surface Areamentioning
confidence: 99%
“…Biofauling of sessile organisms on pumice stones rafting near Okinawa Island Some pumices observed on the Okinawa beach had already become habitats for sessile organisms (Fig. 4), as reported in previous studies [21][22][23][24][25]. Goose barnacles (Lepas sp.)…”
Section: Changes In the Coastal Landscape: Natural Beaches And Estuariessupporting
confidence: 68%
“…If the symbiotic relationship breaks down, the coral tissue will turn white (bleaching), and in the worst case, the coral will die [44,45]. Previous studies discussed that pumice rafts contribute to coral dispersal [21][22][23][24], and rafts may support escape of juvenile coral from unfavorable conditions such as local stress [25]. But the negative aspects of pumice drift are still unclear.…”
Section: Impacts On Shes and Other Organisms In Coastal Watersmentioning
confidence: 99%
“…To date the majority of studies on the Havre 2012 submarine eruption have focused on the limited volume (< 0.1 km 3 or 7% of the total eruptive material) seafloor eruptive products (e.g., Carey et al, 2014Carey et al, , 2018Manga et al, 2018a,b;Ikegami et al, 2018;Mitchell et al, 2018Mitchell et al, , 2019Murch et al, 2019). Studies on the volumetrically dominant pumice raft (∼1.4 km 3 or 93% of total eruptive material) has been at a reconnaissance level, examined limited material (e.g., Rotella et al, 2015;Manga et al, 2018b) and focused on raft dispersion (e.g., Jutzeler et al, 2014;Carey et al, 2014;Velasquez et al, 2018). One outcome of the seafloor-focused studies has been the interpretation that the giant seafloor pumice and pumice raft were erupted contemporaneously (Manga et al, 2018a,b) given near identical whole-pumice compositions, similar mineralogy (i.e., plagioclase, orthopyroxene, clinopyroxene and Fe-Ti oxides) and textural features (e.g., banded pumice, tubed pumice and bread crusting).…”
Section: Havre 2012 Submarine Eruption and Sampling Locationsmentioning
confidence: 99%